2003
DOI: 10.1016/s0926-860x(02)00422-2
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory behaviour during the oxidation of methane over palladium metal catalysts

Abstract: Oscillatory reactions over palladium foil and wire catalysts during the oxidation of methane have been investigated over a wide range of reaction temperatures and argon/methane/oxygen feed gas compositions. Characterisation of the catalyst has also been carried out using scanning electron microscopy (SEM) techniques, which revealed the presence of a porous surface. This suggested that the metal surface has undergone a change since the reaction commenced, and using X-ray powder diffraction (XRD) techniques the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 34 publications
1
30
1
Order By: Relevance
“…Bychkov et al [21] also suggested the deposition/desorption of carbonaceous compounds on the catalysts' surfaces is directly related to a self-oscillatory process they investigated in the oxidation of methane and ethane. Along with Deng et al [15] and Zhang et al [16], they additionally correlated the oscillatory behaviour to changes in the oxidation state of active phase constituents. Therefore, and for a better understanding of changes occurring at the surface of the catalyst, it was inevitable to conduct operando DRIFT measurements throughout the whole duration of the catalytic test.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Bychkov et al [21] also suggested the deposition/desorption of carbonaceous compounds on the catalysts' surfaces is directly related to a self-oscillatory process they investigated in the oxidation of methane and ethane. Along with Deng et al [15] and Zhang et al [16], they additionally correlated the oscillatory behaviour to changes in the oxidation state of active phase constituents. Therefore, and for a better understanding of changes occurring at the surface of the catalyst, it was inevitable to conduct operando DRIFT measurements throughout the whole duration of the catalytic test.…”
Section: Resultsmentioning
confidence: 88%
“…Other works by Zhang et al [17,18] concluded that oscillations may also be observed when using metallic nickel or cobalt foils. However, their intensities and frequencies were lower than what had been observed with palladium [16]. Furthermore, Bychkov et al [19][20][21] confirmed the latter results through witnessing self-oscillations on Pd-supported and Ni-supported catalysts as well as metal foils (Ni and Co).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Its use in industrial process may give a new turn to the progress of new technologies [3]. Palladium as a catalyst is used in various industrial processes Petrolium cracking [4], alkaline oxidation, selective low oxide formation [5,6], reduction of C≡C to C=C without further reduction to carbon-carbon single bond (known as Landler's Catalyst) [7], Suzuki coupling [8], Heck reaction [9] and carbonfluoride bond formation [10]. For the oxidation of alcohols palladium is considered excellent electro-catalyst in alkaline medium [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This observation agreed with what has been reported elsewhere. [10] As the reaction proceeded to higher temperatures, catalytic activity increased for all the samples. On the other hand, Ni-based catalysts revealed a similar catalytic trend to that of Pd-based samples when Ni was reduced prior to reaction and showed general rise in catalytic activity with increased temperature ( Figure 3A) at 400°C.…”
Section: Catalytic Activitymentioning
confidence: 93%